2016
DOI: 10.1038/srep33650
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the Hsp70 family in moss and evaluation of their functions in abiotic stress responses

Abstract: The 70-kD heat shock proteins (Hsp70s) are highly conserved molecular chaperones that play essential roles in cellular processes including abiotic stress responses. Physcomitrella patens serves as a representative of the first terrestrial plants and can recover from serious dehydration. To assess the possible relationship between P. patens Hsp70s and dehydration tolerance, we analyzed the P. patens genome and found at least 21 genes encoding Hsp70s. Gene structure and motif composition were relatively conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 56 publications
(71 reference statements)
2
42
0
Order By: Relevance
“…Both in mammals and plants, ROS (reactive oxygen species) directly impact HSF oligomerization. ROS are acting as second messengers in a great variety of stresses and H 2 O 2 induces binding of high molecular weight protein complexes on HSEs (Volkov et al, 2006) and trimerization of HSFA1a was shown to occur upon treatment with H 2 O 2 , heat or pH variation . ROS action on transcription factors often depends on the oxidation of one or several Cys residues, but a number of other amino acids could also be potential targets of H 2 O 2 (reviewed in Driedonks et al (2015)).…”
Section: Transcriptional Control Of Hspsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both in mammals and plants, ROS (reactive oxygen species) directly impact HSF oligomerization. ROS are acting as second messengers in a great variety of stresses and H 2 O 2 induces binding of high molecular weight protein complexes on HSEs (Volkov et al, 2006) and trimerization of HSFA1a was shown to occur upon treatment with H 2 O 2 , heat or pH variation . ROS action on transcription factors often depends on the oxidation of one or several Cys residues, but a number of other amino acids could also be potential targets of H 2 O 2 (reviewed in Driedonks et al (2015)).…”
Section: Transcriptional Control Of Hspsmentioning
confidence: 99%
“…The amount of free HSPs is the sensor of the cell capacity to maintain a stable proteome and feeds back on its own production. Indeed, in unstressed tissues, the commonly accepted 'chaperone titration model' specifies that HSFs are sequestered by HSP70/90 and maybe other chaperones (Guo et al, 2001;Volkov et al, 2006). Strong evidences obtained in tomato suggest that an increase in SlHSP70/90 clients leads to liberating HSFs, allowing high HSP and HSF production.…”
Section: Transcriptional Control Of Hspsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these families, HSP70 family is the highly conserved and the most researched gene family [11,15,17,[20][21][22][23][24]. Studies have demonstrated that heat stress [15,[18][19][20][24][25][26][27][28][29][30][31][32], Cold stress [15,24,26,29,30], water stress [22,25,26,33,34], oxidative stresses [19,20,22], heavy metals [9,12,13,35], salt stress [13,19,20,22,34], light stress [27], and chemical contaminants [11,15,18,19,25,[35]…”
Section: Introductionmentioning
confidence: 99%